Supply, installation, testing & commissioning of Davit Arm for 13 storied Brac University new campus building at holding no. Kha 224, Merul Badda , Dhaka -1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Fabcons Techno to supply, installation, testing & commissioning of Davit Arm for 13 storied Brac University new campus building project.